Evaluation of clinical guidelines for otitis and impacted earwax: an analysis of quality and treatment proposals - Galvão Alvares, Matheus; da Costa Vaz, Francisca Lumara; Santos Santana, Rafael; Fonseca Lima, Rodrigo; de Oliveira Barbosa, Ana Paula; Gomes, Rosângela Maria (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To evaluate the methodological quality and treatment profile of clinical gui delines for the management of otitis and impacted earwax. Methods: To identify clinical guidelines, a search was carried out in different databases. The selection of evidence went through the peer review process and consensus was used to resolve disagreements. The evaluation was carried out by AGREE II. The criteria adopted to recommend the guideline were the scores found in this domain, with 50% being the minimum expected value. Therefore, guidelines that scored between 30% and 50% in “development rigor” and achieved averages above 50% in two other domains were considered recommended, with modifications. The Kappa test was used to evaluate agreement. Results: Six clinical guidelines were selected and evaluated. Among them, five were considered. Items such as applicability, development rigor, editorial independence and stakeholder involvement obtained lower scores. Non-pharmacological therapy is focused on in all guidelines as f irst-line treatment. Symptomatic management mediated by pharmacological therapy is recommended in combination in the second line of treatment. Conclusion: The guideli nes evaluated were assessed with good quality. The need to qualify recommendations in terms of the evidence that supports them is highlighted, as well as to make recommen dations available in an informed manner, reduce conflicting interests and increase the involvement of interested parties, so that the best care for patients is offered.